Shockwave intravascular lithotripsy facilitated percutaneous coronary intervention in patients with calcified coronary artery disease: a systematic review and meta-analysis of observational studies. (14th October 2021) - Kassimis, G; Patoulias, D; Theodoropoulos, K; Papadopoulos, C E; Davlouros, P; Alexopoulos, D; Sianos, G; Ziakas, A; Kanonidis, I; Banning, A
Abstract: Background: Percutaneous coronary intervention (PCI) outcomes for patients with significant coronary artery calcification (CAC) have been consistently inferior compared to patients without significant CAC. Shockwave Intravascular Lithotripsy (S-IVL) system offers a novel option for lesion modification of severely calcified plaques but supporting evidence on safety and efficacy of this technology is narrow. The aim of this study is to assess S-IVL safety and efficacy in patients with severe CAC undergoing PCI. Methods: We systematically searched MEDLINE, ClinicalTrials.gov and the Cochrane Library to identify studies assessing the efficacy and safety of S-IVL in adult patients with calcified coronary artery disease undergoing PCI. We excluded those studies assessing the effect of S-IVL in patients with under-expanded coronary stents and/or in-stent restenosis. Results: The largest meta-analysis to date was performed. All studies were observational since no relevant randomized controlled trials have been published so far. Nine studies were included in our qualitative synthesis, while 7 of them, in a total of 794 enrolled patients, were used in the quantitative synthesis. Frequency of peri-procedural outcomes of interest was low: a) coronary dissection: 2.52%, b) coronary perforation: 3.0%, c) MI: 3.51%. Relative frequency of 1-month MACE was 5.59% and cardiovascular death 1.01%. S-IVL resulted in a significant increase in the in-stent post-IVL minimum lumen diameter by 1.67 mm, a significant decrease in the in-stent post-IVL vessel diameter stenosis by 53.60%, and a significant increase in the in-stent post-IVL acute gain by 1.68 mm. OCT analysis confirmed a significant decrease in area stenosis post-IVL by 19.71% and calcium angle by 22.14o and a significant increase in lumen area by 1.62 mm 2, without however affecting maximum calcium thickness. When we compared post-stent post-IVL vs. pre-stent post-IVL OCT results, we demonstrated a further significant decrease in area stenosis by 35.89% and in calcium angle by 20.33o, a significant increase in lumen area by 2.74 mm 2 and a neutral effect on maximum calcium thickness. Conclusion: Shockwave Intravascular lithotripsy offers a significant improvement in coronary lumen to facilitate stent delivery and deployment in severely calcified coronary arteries. Although S-IVL appears to be associated with a low incidence of complications and MACE based on our present findings, further evidence from RCTs and longer-term follow-up is required to advocate its routine use in patients with severe CAC. Funding Acknowledgement: Type of funding sources: None.